Competitive drivers for improving future business performance - Martins, Carlos, 1961-; Rodrigues, Paula Cristina Lopes, 1970- (Advances in business strategy and competitive advantage., 2021)
"This book examines conceptual, theoretical, and applied advancements of how to improve competitive performance in an era of uncertainty"--